Sample of Reflective Learning Material Using Quizziz for Learning News Item Text - Wahyu Firmansyah; Ikhsanudin Ikhsanudin; Sumarni Sumarni (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to develop a reflective learning material of news item text for grade twelvestudents using Quizziz. This research was conducted with a focus on how the product was developed.The research methodology used was development research by David Jolly and Rod Bolitho (2011). Thestages used in this research include, Identification, Exploration, Contextual Realization, PedagogicalRealization, and Physical Production. The participants in this study were 20 class XII students at SMAN 9 Pontianak and English teacher. This research used open-ended questionnaire and internalevaluation. Quizziz was used as the main media in creating this product. This product is made as alearning quiz that is in accordance with the TPACK teaching framework. In summary, the product aswell as the materials have been well developed and in accordance with the learner needs.